ANALISIS FAKTOR DALAM KEPUTUSAN PEMBELIAN REPTIL EKSOTIS CV. KURAKU INDONESIA - Lo, Steven (PERFORMA, 2021)
The trend of raising exotic animals in Indonesia is increasing as indicated by the total imports of live animals in July 2020 reaching more than 52 million USD. Furthermore, the data show that the most imported animal species is turtles. As an importer of turtle reptiles, CV. Kuraku Indonesia needs to do research related to the decline in sales turnover in 2020. This study aims to determine what factors contribute to the purchase decision of tortoise reptiles. The data analysis method used is exploratory factor analysis. The research data was obtained via google form which was distributed through the WhatsApp application to 109 sample customers. The results of data processing with the SPSS 20.0 program indicate that there are 4 main factors that influence the purchase decision of turtle reptiles. These factors include: (1) the pleasure factor; (2) regulatory and trust factors; (3) popularity factor; and (4) personal status factors. These four factors as a whole can explain 72.601% customer decisions to buy turtle reptiles.